FRI0066 Leflunomide inhibits proliferation and differentiation of pro-inflammatory th1 cells. (1st June 2001) - Dimitrova, P; Skapenko, A; Schleyerbach, R; Herrmann, M; Kalden, JR; Schulze-Koops, H
Abstract : Background: Leflunomide has been recently introduced as a new treatment for rheumatoid arthritis. It has been shown that this immunomodulatory drug blocks the de novo pyrimidine synthesis by inhibiting the enzyme dihydroorotate dehydrogenase. However, the functional consequences of this action for T cells are still unclear. Objectives: To evaluate the effect of leflunomide on the proliferation and differentiation of human naive CD4 pos T cells isolated from cord blood and of memory CD4 pos T cells isolated from peripheral blood of healthy individuals. Methods: The proliferative response of naive and memory T cells activated with anti-CD3 and anti-CD28 was determined by incorporation of 3 H-thymidine into newly synthesised DNA. The impact of leflunomide on T cell differentiation was assessed in an in vitro system in which effector cells were generated after short term priming. T cell differentiation was induced by priming with anti-CD3 and anti-CD28 in the presence or absence of leflunomide. The phenotype of freshly isolated and primed T cells was determined by cytometric analysis of intracellular cytokines. Results: Leflunomide inhibited T cell proliferation induced by stimulation with anti-CD3 and anti-CD28 in a dose-dependent manner in naive and memory CD4 pos T cells. Moreover, the expression of the activation markers CD25, CD69 and CD40L was markedly suppressed. Leflunomide significantly decreased the frequencies of T cells capable of producing IFN-γ. Most interestingly, the generation of Th2 effectors was enhanced by leflunomide in some donors. Conclusion: Leflunomide may exert its anti-inflammatory effect by preventing the proliferation of pro-inflammatory Th1 effectors and by switching the T cell differentiation from the Th1 to the Th2 direction.